A Systematic Review: Mindfulness Applied on the Field of Tourism - Iacob, Vivien; Neves de Jesus, Saúl; Carmo, Cláudia (Journal of Tourism, Sustainability and Well-being, 2021)
More advanced systematic reviews and traditional literature reviews have been an important point in assessing the epistemological progress of any field. Mindfulness has been described as a process of bringing attention to moment-by-moment experience. In recent years, some researchers have established the influence of mindfulness on the tourists’ experience, and it has been gaining a growing interest. Several studies revealed numerous psychological benefits including mental ease, tranquility, relaxation, and well-being when tourists embrace a mindfulness state. Despite this, a systematic review of this topic has not been conducted. Our main goal is to synthesize the existing studies about mindfulness in the tourism area, to provide an overview of how mindfulness has been conducted, and to explore what are the main outcomes. A literature search was undertaken using four electronic databases, namely Science Direct, PsycInfo, PubMed, and Web of Science. Quantitative and qualitative studies were included. All studies in the review used the mindfulness concept applied in the field of tourism. Using PRISMA guidelines, from a total of 517 records initially identified, 16 studies were selected for the review (n = 4240 participants). The reviewed literature suggested that mindfulness is effective in improving positive travel experiences, satisfaction, loyalty, happiness, well-being, and positive psychological and physical benefit. Mindful tourists are more responsive to sustainability practices and tend to be more connected to heritage sites. Mindfulness can be considered as a relevant concept that provides positive outcomes and may help to better understand the benefits derived by the tourists from traveling. Still, more research is needed to determine the efficacy and to clarify the contribution of processes of mindfulness to observed outcomes.